APPLICATION OF FOREIGN EXPERIENCE IN THE ORGANIZATION OF MANAGEMENT COST ACCOUNTING - Khamidova S.Y. (Scholar Express Journals, 2023)
The processes of transition to international financial reporting standards are highlighted
Keywords: Business language; international markets; economic indicators